Meta-analysis of mortality factors after COVID-19 infection in pediatric oncology patients - Liu, Qingchen; Wang, Xia; Zhou, Xueqin (Frontiers in Oncology, 2025)
ObjectiveThere are few clinical studies related to COVID-19 in pediatric cancer patients, and systematic reviews or meta-analyses on its mortality risk factors are particularly lacking. Therefore, we conducted this meta-analysis to systematically analyze the mortality risk factors of pediatric cancer patients after COVID-19 infection, providing effective evidence-based medical evidence for epidemic prevention and control and clinical treatment of pediatric COVID-19 patients.MethodsElectronic databases of PubMed, Embase, Cochrane Library and Web of Science were searched using “cancer” “COVID-19” “children” “mortality” related subject headings and keywords. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the included studies. Outcomes included age, weight, clinical complications in patients, cancer type, consolidation of cancer treatment, and critical illness. The quality of observational studies was assessed using the Newcastle-Ottawa Scale, which includes criteria such as study population selection, comparability, and evaluation of exposure or outcome, by two independent reviewers.ResultsA computerized search of the literature yielded six observational studies with a total of 2,696 patients, and a pooled assessment of predictive factors revealed that the occurrence of adverse clinical complications, the presence of solid tumors, and the presence of acute and critical conditions significantly increased mortality in pediatric oncology patients (P < 0.05), although, overall, aggressive consolidation of cancer treatment significantly reduced the death of patients. Although overall,being in the cancer consolidation treatment period is significantly associated with a reduced risk of patient mortality, there is still an increase in mortality with Radiotherapy, possibly due to immunocompromise (P < 0.05), whereas Immunotherapy and Surgery do not affect patient prognosis. Subgroup analyses showed that prolonged consolidation of cancer treatment reduced mortality. The sensitivity analysis of the results of the outcome indicators was stable with low sensitivity and high confidence.ConclusionAdverse clinical complications, the presence of solid tumors, and the occurrence of critical conditions increase mortality in pediatric cancer patients. Receiving aggressive cancer treatment is associated with lower mortality rates, but this association should be interpreted with caution, as it may be confounded by other factors.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420250570932.